Correlation of Untreated Dental Caries and Oral Health-Related Quality of Life Amongst School Children: A Cross-Sectional Study - Shantanu Deshpande; Laresh Mistry; Madhura Shekatkar; Supriya Kheur; Sumeet Agarwal; Sanpreet Singh Sachdev (Journal of Pharmacy and Bioallied Sciences)
Introduction: Untreated dental caries can drastically affect a child’s oral health-related quality of life (OHRQoL). This study aimed to evaluate the prevalence of untreated caries and their impact on children’s quality of life. Materials and Methods: The oral cavity of 640 children aged 12-15 years attending municipal corporation secondary schools was examined using the PUFA index. OHRQoL was assessed with the Child Oral Health Impact Profile - Simplified (COHIP-SF) questionnaire, comprising 19 questions. Results: The mean PUFA score was 0.98 ± 1.356, and the mean COHIP total score was 15.32 ± 11.34. The total COHIP score exhibited a strong negative correlation (correlation coefficient = -0.80) with the PUFA score. Conclusion: Higher PUFA scores had detrimental effects on quality of life, with the greatest concerns in socio-emotional well-being and self-image.